A PERSPECTIVE ON COACHING AND ITS INTEGRATION INTO THE ANTHROPOLOGICAL CONTEXT OF SPORT COMPETITION. CASE STUDY: ROMANIAN 3ᴿᴰ LEAGUE, FOOTBALL - Andrei-Gabriel ANTONESCU; Silvia TEODORESCU; Monica Iulia STĂNESCU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2023)
The Romanian 3rd Football League is a socio-cultural universe of its own. The large number of participants (teams, players, technical-administrative staff, supporters, etc.), the fact that it takes place in a predominantly rural or small-town setting and its heterogeneous nature give it a specific diversity. Being a coach in this environment is a challenge. Merayo (2021) believes that the coach has to be part of the team, the club and the culture they are part of. However, in Romania’s 3rd league, coaching can be considered a veritable art, with circumstances not found in any other sporting context. Coaches change very often, are caught between the same teams, having to radically change their perspective on a team, a player or a context in an extremely short time. Microsystem, mesosystem, exosystem and macrosystem are part of a model proposed by Bronfenbrenner (1976, 1987), and still considered relevant in the sport context by Merayo (2021). We also identify this in the 3rd league. The third league coach spends his whole life caught between these systemic units. And yet the whole coaching process must be seen as part of a competition with strong anthropological valences. So, is it the specific culture of third league football that is best developed in rural or small-town environments, or does the environment of these towns generate the culture of the third league and is it, in fact, a culture of theirs translated into football?